Coating of NIL printed polymeric templates with semiconductor nanoparticles in solution for the preparation of anisotropic inorganic structures - Mohamed-Noriega, Nasser; Mondin, Giovanni; Grothe, Julia; Kaskel, Stefan (Materials Chemistry and Physics, 2016)
Anisotropic structures possess unique direction-dependent properties that are hard to obtain by changing the diameter of a spherical particle; therefore, they are of great interest for a variety of applications. The secret lies on the appropriate selection of shape, size and composition; however, the control over these variables is not always a straightforward process. Template-based synthesis methods simplify the process since the template defines shape and size. Physical methods to pattern offer an extra degree of flexibility, since almost any shape can be fabricated. Thus, in this work, it was demonstrated for the first time that patterned structures prepared by soft lithography (PMMA 10, 5, 0.5 μm lines and 20/10 μm rings) can be easily detached from the substrate, dispersed and used as template to prepare custom made inorganic materials (ZnS:Mn and ZnO) in the microscale, with some characteristic dimension even in the nanoscale (thickness and cross-section), utilizing solution-based synthesis methods, as being established for the synthesis of nanoparticles. Uniform coatings were obtained at the faces of the structures, but with minor defects at the edges. The use of ex-situ synthetized nanoparticles to coat the templates produced a coating consisting of compactly packed nanoparticles, while the in-situ approach resulted in a rougher coating of packed nanoparticles and nanorods. Compact and hollow structures were obtained after the removal of the templates thermally and with acetone, respectively. Generally, after removal of the template, the final size of the structures was smaller, allowing the preparation of nanostructures starting from micro-templates. The novelty of this work is given by the flexibility of pattering techniques to fabricate custom-made structures and on the utilization of such structures as templates to prepare inorganic structures.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Anisotropic structures; Nanoimprint lithography; Solution-based synthesis; Template-based